Profile and Outcome of Adult Spine Pathologies Managed in a Neurosurgical Tertiary Care Center in Nepal - Sah, Hemant K; Shrestha, Dipendra K; Rajbhandari, Binod; Sedain, Gopal; Pradhanang, Amit B; Shilpakar, Sushil K; Sharma, Mohan R (Journal of Institute of Medicine Nepal, 2020)
Introduction Spine pathology involves a wide spectrum of diseases and needs a multidisciplinary approach including surgery, rehabilitation and psychological support. It increases the burden to the family and society. This study describes diseases related to spine and spinal cord from a neurosurgical department of a tertiary hospital in Nepal. Methods This is a retrospective study of all spinal cases admitted between April 2019 to February 2019, in the Department of Neurosurgery, Tribhuvan University Teaching Hospital, Kathmandu, Nepal. All adult patients of ≥16 years, diagnosed with various spinal diseases were included. Based on the spectrum of causative pathologies, the study population was broadly categorized into trauma, degenerative, tumor, vascular and infection. Demographics, other variables, and outcome at 1 month were assessed. Results A total of 71 patients were included in this study. Male preponderance was observed in all categories. Twenty three patients (32.4%) had traumatic spine injury and fall from height was the most common mode of injury, accounting for two-third of the total spinal trauma patients. Cervical segment was involved in two-third patients. More than one-third of the spinal patients (36.6%) had a degenerative disorder involving lumbar (57.7%) and cervical regions (42.3%). Spinal infection was diagnosed in 11.2% of the patients with 62.5% diagnosed as Pott’s spine. Overall complications were seen in 20%. Pain improved in all patients while overall good outcome was noted in 63.2% of the patients. Conclusion Our study demonstrated a large patient burden and a clinical profile dominated by preventable causes such as RTA and fall injury. With early treatment and rehabilitation, significant improvement can be achieved. Further large scale multicenter studies are required to generalize the findings of this study to the whole population of Nepal.